2006
DOI: 10.1002/hbm.20293
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate‐induced activation of the anterior cingulate but not the striatum: A [15O]H2O PET study in healthy volunteers

Abstract: The dopaminergic system has been implicated in the pathogenesis and treatment of a variety of neuropsychiatric disorders, such as schizophrenia, depression, and addiction. (Dys)function of the dopaminergic system may be studied by combining [15O]H2O PET with a dopaminergic drug challenge. In this pilot study we investigated the suitability of the dopamine reuptake blocker methylphenidate (MP) as a dopaminergic probe. Measurements of regional cerebral blood flow (rCBF) were made at 10 and 30 min after placebo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 119 publications
(145 reference statements)
6
25
0
Order By: Relevance
“…The radiotracer 18 F-fallypride, however, is able to estimate DRD2/3 BPnd in PFC, temporal lobes, and the insula in addition to the striatum (Mukherjee et al , 2002; Riccardi et al , 2008) and can index DA release after d-amphetamine (dAMPH) administration, measured as %ΔBPnd from baseline (Riccardi et al , 2006a; Slifstein et al , 2010). We were particularly interested in using fallypride to test whether DA functions in paralimbic cortical areas, specifically the mPFC/OFC, related to subjective responses to dAMPH given past evidence that activity in these areas are increased in response to psychostimulants in drug naïve individuals (Vollm et al , 2004) and correlate with their self-reported euphoric effects (Udo de Haes et al , 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The radiotracer 18 F-fallypride, however, is able to estimate DRD2/3 BPnd in PFC, temporal lobes, and the insula in addition to the striatum (Mukherjee et al , 2002; Riccardi et al , 2008) and can index DA release after d-amphetamine (dAMPH) administration, measured as %ΔBPnd from baseline (Riccardi et al , 2006a; Slifstein et al , 2010). We were particularly interested in using fallypride to test whether DA functions in paralimbic cortical areas, specifically the mPFC/OFC, related to subjective responses to dAMPH given past evidence that activity in these areas are increased in response to psychostimulants in drug naïve individuals (Vollm et al , 2004) and correlate with their self-reported euphoric effects (Udo de Haes et al , 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In a spatial working memory task, the MPH-induced improvements in task performance are accompanied by task-related reductions in regional cerebral blood flow (rCBF) in the dorsolateral prefrontal cortex and posterior parietal cortex in healthy males [19] . MPH activates the anterior cingulate but not the striatum according to a [ 15 O]H 2 O PET study in healthy volunteers [20] . There are also some studies in which the MPH effects were evaluated using functional magnetic resonance imaging (fMRI).…”
Section: Introductionmentioning
confidence: 99%
“…10 for review). For example, studies have shown that stimulants alter cerebral activation and influence cognitive functions, including improving inhibitory control, in healthy individuals (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Similarly, Overtoom et al (22) reported that methylphenidate improved stopping performance and restored the electrophysiological potential of stopping in a stop signal task, whereas it did not affect go trial reaction time, in adult patients with ADHD.…”
mentioning
confidence: 99%